Diffusion kinetics governing the diffusivity and diffusion anisotropy of alloying anodes in Na-ion batteries - Park, Jun-Hyoung; Choi, Yong-Seok; Byeon, Young-Woon; Ahn, Jae-Pyoung; Lee, Jae-Chul (ELSEVIER, 2019)
Diffusion in alloying anode materials was previously viewed as solute diffusion in conventional alloys. However, solute diffusion, neglecting the presence of a thin intermediate reaction layer between the unreacted anode material and inflowing carrier ions, is insufficient to account for the diffusion kinetics in alloying anodes and their influence on the electrochemical properties of batteries. Here, by performing a comparative study on Na-Sb and Na-Sn battery systems displaying differing diffusion kinetics, we establish the relationship between diffusion kinetics and electrochemical properties for batteries. In situ microelectrochemical experiments show that sodiation in Na-Sb and Na-Sn systems is governed by an interface-controlled reaction (ICR) and a diffusion-controlled reaction (DCR), respectively, causing them to display significantly different diffusion rates, diffusion anisotropy, and possibly self-limiting diffusion of carrier ions. Density functional theory calculations are performed to elucidate the structural origin of the observed diffusion behaviors. It is found that the different degrees of structural stability evaluated for the propagating interfaces of the two systems are responsible for the differing diffusion kinetics, which in turn determine the respective diffusion rates and diffusion anisotropy of the anode materials. The present study provides crude yet quantitative guidelines for selecting battery materials and can be used to develop fast-charging batteries with high stability and improved cycle life.